1974
DOI: 10.1038/icb.1974.70
|View full text |Cite
|
Sign up to set email alerts
|

The Origin of Immunoglobulins in Intestinal Secretion of Sheep

Abstract: Summary. Studies were made on the origin and mechanism of transfer of IgGj, IgG.,, IgA and IgM into the secretion of isolated loops of jejunum of unanaesthetized sheep. IgA was the major immunoglobulin in intestinal secretion, although considerable quantities of IgGj and IgG^ were also present. Secretion: serum radioactivity ratios for IgGj^ and igG^ were similar, indicating that they were transferred into intestinal secretion with equal facility. Specific radioactivities of the various immunoglobulins in seru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

1976
1976
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 7 publications
0
12
0
Order By: Relevance
“…Parasitespecific IgG1 controls H. polygyrus in mice through antibody-dependent activation of macrophages (Esser-von Bieren et al, 2013) and specific binding to parasite excretory-secretory antigens (Hewitson et al, 2015). It is possible that similar IgG-dependent mechanisms of anti-nematode immunity occur in sheep, particularly as IgG1 is prominent at mucosal surfaces in sheep (Cripps, Husband, & Lascelles, 1974).…”
Section: We Examined Between-individual Variation In Fec Within a 4-mentioning
confidence: 99%
“…Parasitespecific IgG1 controls H. polygyrus in mice through antibody-dependent activation of macrophages (Esser-von Bieren et al, 2013) and specific binding to parasite excretory-secretory antigens (Hewitson et al, 2015). It is possible that similar IgG-dependent mechanisms of anti-nematode immunity occur in sheep, particularly as IgG1 is prominent at mucosal surfaces in sheep (Cripps, Husband, & Lascelles, 1974).…”
Section: We Examined Between-individual Variation In Fec Within a 4-mentioning
confidence: 99%
“…Such antibodies may be transferred from the serum back into the intestine, accounting for the persistence of IgG1 fecal antibodies after termination of colostrum feeding and providing transient passive protection. Other studies have documented the transport of serum lgG1 into the intestine in both sheep and cattle (15,46). Studies also indicated passively acquired serum rotavirus antibodies, in high titer, could protect against rotavirus-associated diarrhea in lambs (67), and high serum Ig concentrations correlated with absence of diarrhea in young calves (33).…”
Section: Passive Immunity Against Type 1 Viruses: Lactogenic Immunitymentioning
confidence: 99%
“…The similar half-life of IgG1 in calves and in alder cattle suggests that a similar clearance mechanism is operating (Butler, !983;Nielsen et al, 1978;Husband et al, 1972). IgG transfer to the intestine has also been reported in other species: mouse (Fubara and Freter, 1972), rat (Wu and Walker, 1976), rabbit (Fubara, 1972;Wernet et al, 1976), dog (Anderson et al, 1963;Pierce and Reyqoldc, 1974), and sheep Cripps et al, 1974). In si~eep, Cripps et ~l.…”
Section: Discussionmentioning
confidence: 84%